2012
DOI: 10.1080/09297049.2011.602012
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral problems, cognitive difficulties and quality of life in children with epilepsy: An analysis of parental concerns

Abstract: In cognitively impaired or young children with epilepsy, only proxy-report can be used for the assessment of Quality of Life (QOL) and behavior. The present study aims to propose proxy QOL tools applicable in all children with epilepsy and to examine the impact of epilepsy characteristics (e.g., age of onset of epilepsy, epilepsy syndrome) and child's age and situation (in mainstream school or in special institution). We studied 219 children with various types of epilepsy with and without cognitive impairment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 70 publications
3
6
2
Order By: Relevance
“…Sabbagh et al found that early onset of seizures increased the likelihood of the child being excluded from mainstream schooling 16 . Soria et al, reported that the age of onset of seizures was associated with depression, so the earlier the onset of seizures, the more the depressive symptoms the patient presented 15 , whereas we noted, that was associated with poor quality of life and bad sociability.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Sabbagh et al found that early onset of seizures increased the likelihood of the child being excluded from mainstream schooling 16 . Soria et al, reported that the age of onset of seizures was associated with depression, so the earlier the onset of seizures, the more the depressive symptoms the patient presented 15 , whereas we noted, that was associated with poor quality of life and bad sociability.…”
Section: Discussioncontrasting
confidence: 49%
“…We assessed children aged 3 to 16 years as was done by Soria et al 15 and Sabbagh et al 16 , because the age below 3 years represents preschool age. Above 3 years of age, the behavior of these children could be evaluated at home and in the school environment, and observing these disorders in the two environments makes it possible to pose the diagnosis as recommended by the DSM IV.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these children were having difficulty to concentrate for a longer period of time or difficulty in comprehending the subject because of having seizures for so many years. Soria and colleague [20] in their study has found that children with epilepsy has associated problems like learning difficulties or cognitive impairment, difficulty to concentrate along with behavioral problems.…”
Section: Discussion:-mentioning
confidence: 98%
“…Early onset of seizures is often associated with lower functioning and poorer cognitive [6][7][8][9] and behavioral/emotional outcomes. 10 The known associated behavioral and emotional dysregulation 11,12 can also further negatively impact cognitive development. Not surprisingly, poor pharmacological seizure control is associated with worse cognitive outcomes, particularly in infants and young children.…”
Section: Epilepsy In Young Childrenmentioning
confidence: 99%